FUNGSI MANAJEMEN UNTUK SISTEM SURVEILANS DEMAM BERDARAH DENGUE (DBD) DI PUSKESMAS BANGKINANG KOTA KABUPATEN KAMPAR TAHUN 2017 - Emdas Yahya; Buchori Lapau; Oktavia Dewi (Universitas Pahlawan Tuanku Tambusai, 2017)
Dengue hemorrhagic fever (DHF) occurences in the local government clinic in Bangkinang city are increasing each year. The increasing of DHF cases may be caused by the weakness of DHF surveillance system in all levels. A good management is surely required in order to keep the surveillance in track. However it may decrease the incidence of dengue and case fatality rate, the implementation of the surveillance also needs to be assessed. Without the assessment of the surveillance system, it can not guarantee that surveillance works well. The aim of this research is determining the relation of management for DHF surveillance system at the local government clinic in Bangkinang city. The research was a non-standard qualitative research using the phenomenology approach. It was executed in July 2017. There was one key informant and three additional informants. the information was collected through depth interview and observation. Then it would be analysed using content analysis method. The result of surveillance system assessment of at the local gorvernment clinic in Bangkinang city was categorized as â€œenoughâ€ and â€œgoodâ€. And the management function do not runs well. Due to incidental planning, inadequate human resource, late epidemiological investigation, no larva monitoring officer, low knowledge and behavior of society and limitations of fogging tools, the incidence of dengue always increased. Local government clinic officer is supposed toÂ improve the implementation of surveillance system along with its implementation management. The formation of larva monitoring officer is also required as well as the improvement of cross-sector coordination and counseling for the improvement of community knownledge.